The acute effects of massage on muscle tone and perceived recovery - Haakana, Piia (2008)
Haakana, Piia 2008. The acute effects of massage on muscle tone and perceived recovery. Department of biology of physical activity, University of Jyväskylä. Bachelor’s thesis. 47 pp. The physiological effects of massage have been controversial in previous studies. There is one previous study on effects of massage on muscle tone but there were no effects during one month intervention. The purpose of this study was to determine the correlations between subcutaneous tissue and rectus femoris muscle thickness and muscle tone. The differences on muscle tone between groups that received massage immediately or one day after the resistance training were examined. The effects of massage on perceived recovery were monitored immediately and day after massage. Ten subjects completed the study, five in each group. The thickness of subcutaneous and muscle tissue, and pennation angle was measured from rectus femoris muscle prior to the training session. Both groups had the same pre measurements and training session, with three sets at 70% of 1 RM squat until exhaustion on a Smith machine. Muscle tone was measured before and after the training and massage sessions, and a day after massage. Subjects filled in questionnaires of their state of perceived recovery each time the muscle tone was measured after the training. Massage was applied for group 1 immediately after the training and for group 2 one day after the training. Massage, 10 minutes per leg, was performed with effleurage and petrissage techniques by the same therapist for each subject. A significant decrease in muscle tone was found in group 1 immediately after training. Following massage the tone increased. There was no effect of training or massage on group 2. This might be due lack of subjects and the control group, insufficient training session, incapability of subjects to totally relax during the muscle tone measurement or other factors such as elevated muscle tone due to activities prior to the measurements.